Strategic workouts: the rationale for Southeast Asian states' military exercises with China - Seow, Ian Cheng Wei (2024)
Conventional arguments of deterrence and the balance of power do not satisfactorily explain Southeast Asian states’ joint military exercises with China. Instead, the more likely reasons are the use of these drills by some Southeast Asian states to signal their neutrality in the US-China geopolitical competition and to deflect US criticism of their governance and human rights record.